Hydrostatic pressure analysis of yarn composites patch for PVC pipes / Jamaliah Md Said ... [et al.] - Md Said, Jamaliah; Abdul Rahman, Noor Leha; Jumahat, Aidah; Mohd Zahib, Zaidahtulakmal; Mahadzir, Muhammad Zarief Iman (UiTM Press, 2025)
The globally high-demand pipeline is prone to operational issues that can be mitigated using composite materials. Damage and cracks in the pipe can lead to structural weakening, leaks, and reduced functionality. This research aims to determine the adhesion strength of polyvinyl (PV) resin through lap joint testing, assess the burst pressure of polyvinyl chloride (PVC) pipes via hydrostatic pressure testing, and evaluate the impact of various wrapping materials on the maximum hydrostatic pressure of damaged PVC pipes. The PVC pipe was introduced to a 20 mm hole diameter as a defect and then patched with woven basalt fiber. The yarn-commingled fiber mat was wrapped onto the PVC pipe surface using the hand lay-up and vacuum bagging methods. Various materials with the same stacking lay-up layer and different fiber orientations were used in this study. Hydrostatic pressure testing on the PVC pipe showed that the bare pipe (unwrapped) can withstand up to 1.5 MPa before failing. For reference materials in the woven fiber type, the highest maximum pressure achieved was approximately 2.03 MPa using the glass chopped strain mat (CSM) and woven fiber for the wrapping system. Among the commingled fiber systems, the basalt (B/B) commingled fiber demonstrated the highest maximum hydrostatic pressure of about 1.86 MPa, with a maximum hoop stress of 26.5 MPa and a strain of 1.37%. This research demonstrates that using composite materials, particularly glass chopped strain mat (CSM), woven fibers, and basalt commingled fibers, significantly enhances the structural performance of damaged PVC pipelines compared to untreated pipes. These findings provide valuable insights into the effective design and selection of fiber composite materials for pipeline repairs, offering durable and innovative solutions to mitigate operational issues in highdemand pipeline systems.